New Collegeville Bible Commentary: Old Testament : Old Testament - Durken, Daniel (Book collections on Project MUSE., 2015)
Concise and accessible, this one-volume edition of the New Collegeville Bible Commentary: Old Testament draws together the individual contributions to the Old Testament series and offers them to readers in a convenient and attractive format. Written by an array of respected scholars, the individual commentaries collected here bring expert insight into the Old Testament to Bible study participants, teachers, students, preachers, and all readers of Scripture. A first-rate, reliable resource for Bible study and reflection, the New Collegeville Bible Commentary: Old Testament answers the Second Vatican Council's call to make access to Scripture "open wide to the Christian faithful."